Tupistra nganii (Asparagaceae), a new species with greenish yellow flowers from northern Vietnam and southwestern China - Averyanov, Leonid V.; Nguyen, Khang Sinh; Nuraliev, Maxim S.; Vislobokov, Nikolay A.; Тanaka Noriyuki; Kopylov-Guskov, Yury O.; Lyskov, Dmitry F.; Maisak, Tatiana V.; Hieu, Nguyen Quang; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Thai, Tran Huy (Phytotaxa, 2020)
Tupistra nganii is described and illustrated as a new species from Ha Giang Province in northern Vietnam and Yunnan Province in southwestern China. The new species is most similar to T. muricata from Thailand and Laos, from which it differs by the greenish white or yellow perianth and longer exserted stamens. Additionally, Tupistra longispica is reinstated on the basis of new morphological evidences.